ALTERNATIF STRATEGI PEMASARAN PADA BATIK BOGOR TRADISIKU MELALUI QSPM - Zaki, Ahmad; Kancana, Sauptika; Tiara Anjelina; Annisa Zulfa, Firdha; Suryono, Zahra Caroline (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
Batik Bogor Tradisiku is one of the batik pioneers in Bogor. This research aims to develop a superior competitive strategy and appropriate business policies for the Batik Bogor Tradisiku business through three stages of analysis methods. The first stage is the input stage, which includes the external factor evaluation matrix (EFE Matrix), competitive profile matrix (CPM), and internal factor evaluation matrix (IFE Matrix). The second stage is the matching stage, consisting of the SWOT and SPACE matrix. The third stage is the decision stage, using a quantitative strategic planning matrix (QSPM). A quadrant 1 position was found through the Input Stage, indicating an aggressive strategy. Furthermore, for the Matching Stage, it is proposed for the SO strategy, namely by developing batik motif designs following developing trends in society, using discount promotion strategies, increasing promotion and marketing through digital media and exhibitions at home and abroad, improving and maintaining the quality of batik products to compete with competitors and maintaining consumer loyalty. Then next, for the Decision Stage through QSPM, it was found that the score for 2 alternative strategies, namely penetrating the market with service development, was 6.60> 6.27, which shows that the right strategy for the Batik Bogor Tradisiku business is to penetrate the market to reach more customers.Keywords: Management Strategy, QSPM, IFAS-EFAS Matrix, SWOT,